ALMA observations of sulfur-bearing molecules in protoplanetary disks. Issue Volume 14:Issue S345(2019) (August 2018) - Nomura, H.; Higuchi, A.; Sakai, N.; Yamamoto, S.; Nagasawa, M.; Tanaka, K.K.; Miura, H.; Nakamoto, T.; Tanaka, H.; Yamamoto, T.; Walsh, C.; Millar, T.J.
Abstract: It is thought that protoplanets formed in protoplanetary disks excite the orbital motion of the surrounding planetesimals, and the bow shocks caused by the highly excited planetesimals heat their icy component evaporating into gas. We have performed model calculations to study the evolution of molecular abundances of the evaporated icy component, which suggests sulfur-bearing molecules can be good tracers of icy planetesimal evaporation. Here we report the result of our ALMA observations of sulfur-bearing molecules towards protoplanetary disks. The lines were undetected but the obtained upper limits of the line fluxes and our model calculations give upper limits of the fractional abundances of x (H2 S) < 10 −11 and x (SO) < 10 −10 in the outer disk. These results are consistent with the molecular abundances in comets in our Solar system.